Microsoft SharePoint Foundation 2010 : step by step - Londer, Olga M.; Coventry, Penelope (Redmond, Wash. : Microsoft Press ; New Delhi : PHI Learning Pvt. Ltd., 2011)
A guide to Microsoft SharePoint Foundation 2010 covers such topics as setting up a team site, capturing and organizing content into libraries, using blogs and wikis, and automating business processes.
Includes index.
Keywords: Intranets (Computer networks); Web servers; Client/server computing; Microsoft Office SharePoint server